Liberating Researchers from the Glovebox: A Universal Thermal Radiation Protocol Toward Efficient Fully Air‐Processed Perovskite Solar Cells (Solar RRL 5∕2019). Issue 5 (3rd May 2019) - Wang, Guoliang; Liu, Changwen; Kong, Weiguang; Chen, Hong; Li, Dedi; Amini, Abbas; Xu, Baomin; Cheng, Chun
Abstract : In article no.1800324, Chun Cheng and co‐workers report on a thermal radiated hot‐cast method (THCM) toward efficient fully air‐processed perovskite solar cells. In the THCM, a zero‐temperature gradient and greatly depressed relative humidity field are well established at the local space above substrates, where oriented and compact perovskite films with a smooth surface and largely sized grains are obtained.